Does the Kuznets curve apply for financial development and environmental degradation in the Asia-Pacific region? - Duc Hong Vo; Nhan Thien Nguyen; Anh The Vo; Chi Minh Ho; Thang Cong Nguyen (Heliyon, 2021)
The Asia-Pacific region has faced conflicting objectives of achieving sustainable economic growth and simultaneously improving environmental quality. This paper, the first of its kind, applies the concept of the Kuznets curve to financial development in this region. The long-term effect of financial development on environmental degradation is examined using a sample of 26 countries in the 2007–2017 period. This paper uses the long-term estimation techniques - the panel autoregressive distributed lag, including the pooled mean group model; the mean group; and the dynamic fixed effect estimator. The second-generation Granger test is used to determine the causality between financial development and environmental degradation. The U-shaped nexus and a bi-directional relationship between financial development and environmental degradation are found.